TINJAUAN YURIDIS PENGENAAN PAJAK E - COMMERCE DI INDONESIA PASCA BERLAKUNYA UNDANG - UNDANG CIPTA KERJA (STUDI KOMPARATIF DENGAN TIONGKOK) - Yemima Yerikha Sekar Wangi, (2022)
At a time of this pandemic, people tend to use e-commerce asa medium to help them make ends meet by online shopping. Moreover, many feel that ecommerce can be used as an opportunity to earn additional income and profit in the face of the difficult economic times of this pandemic. Unfortunately, however, there are still many partners in e-commerce or hawkes-personal traders in ecommerce who do not report their second income to make sure that income is exempted. The type of research used in the composition of this writing isa normative-law study of literature that is done by examining library material or secondary data. The research is expected to provide an understanding to the public, following the regulation on tax adoption of e-commerce by 2020's statute 11 on his special work for the partners of e-commerce, and also in relation to the tax on e-commerce in the country of China, as in Indonesia does not manage the surveillance of e-commerce's transactions while China has been implementing them for years, And China alone has been able to collect the PPN, which is against the Indonesian PPN law, which only entrepreneurs who have been confirmed as tax payers.